Assessment of Land Cover and Water Resources Changes in Igunga District: A Strategy towards Policy Reform and Sustainable District Development (The Journal of Building and Land Development, 2018)
Vegetation cover and water resources play an important role in determining soil characteristics and serves as the energy source for the vast array of animal species. This study is focused in the investigation of the problem of vegetation cover and water resources depletion resulting from increased population pressure and its associated socio-economic activities. The study area is the Igunga District, in Tabora Region. The land area covered by the District is 6,788 Sq-km which is 8.9 per cent of the area covered by the region. The altitude varies from 1000m to 1800m above sea level, and annual rainfall ranges between 500mm and 800mm. Vegetation in this area consists of the grassland and acacia species; hence the District is semi-arid in nature. The objective of this study was to assess and model the vegetation cover and water resources changes that had occurred in between 1985-1990, 1990-1995, 1995-2000 and 2000- 2010 epochs, as the results of increased population pressure and the human socio-economic activities conducted in the study area. The data used for the research was Landsat Satellite Imageries of 1985, 1990, 1995, 2000, 2005, and 2010. The ERDAS Imagine 9.1 Software was used in the pre-processing and processing of the image data. The classification technique used was the Hybrid Classification method, which utilizes both features of unsupervised and supervised classifications. The Accuracy Assessment results for all classified image were above 80%. Change detection was applied to detect changes between the epochs. The findings show that the vegetation cover, especially the forest and woodland cover changed to bush-land vegetation cover type and to bareland This means that, forest and woodlands had a decreasing trend of change while the bushland and bareland had an increasing trend of change. The water resources showed a slight depletion.Key words: Vegetation cover, water resources, sustainability, policy reform.